Risk Modeling for Appraising Named Peril Index Insurance Products : A Guide for Practitioners - Mapfumo, Shadreck; Groenendaal, Huybert; Dugger, Chloe (Washington, DC: World Bank, 2017)
Named peril index insurance has great potential to address unmet risk management needs for agricultural insurance in developing economies, potentially contributing to increased agricultural sustainability and improved food security.